1995
DOI: 10.1128/iai.63.1.175-181.1995
|View full text |Cite
|
Sign up to set email alerts
|

The enterotoxin of Bacteroides fragilis is a metalloprotease

Abstract: During the past decade, strains of Bacteroides fragilis that produce an enterotoxin have been implicated in diarrheal disease in animals and humans. The extracellular enterotoxin has been purified and characterized as a single polypeptide (M r , ϳ20,000). Single specific primer-PCR was used to clone a portion of the B. fragilis enterotoxin gene. The recombinant protein expressed by the cloned gene fragment reacted with monospecific antibodies to B. fragilis enterotoxin by enzyme-linked immunosorbent assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 38 publications
5
87
0
1
Order By: Relevance
“…Currently, there is valuable structural and functional information for FRAs [6,[8][9][10][11]. The crystal structure of FRA3 was recently reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is valuable structural and functional information for FRAs [6,[8][9][10][11]. The crystal structure of FRA3 was recently reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…B. fragilis is known to produce several proteases [26], and more recently a metalloprotease enterotoxin [27] and a ¢brinogen-degrading serine protease [28] have been described. A trypsin-like protease is also produced by the related Bacteroides forsythus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence, invasion, and production of enzymes or toxins which assist in invasion or destruction of tissue or survival of organisms are potentially significant in the understanding of pathogenesis. Different kinds of virulence factors of B. fragilis such as capsules (33,34,38), fimbriae (40,42), neuraminidase (1,35,41), iron uptake (36,37,46), superoxide dismutase (14), and enterotoxin (27,30,31,45), have been characterized. However, up to now, the critical role of proteases in infectious diseases has been unclear in B. fragilis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enterotoxigenic strains of B. fragilis were isolated and the enterotoxin from one of them was purified (29,30,44). In addition, Moncrief et al (27) reported that the enterotoxin of B. fragilis is a zinc metalloprotease. Therefore protease production by B. fragilis has recently been the focus of intense research interest from the viewpoint of both biochemistry and pathogenicity.…”
mentioning
confidence: 99%